2018
DOI: 10.1177/1071100717746181
|View full text |Cite
|
Sign up to set email alerts
|

Role of Subtalar Arthroscopy in Operative Treatment of Sanders Type 2 Calcaneal Fractures Using a Sinus Tarsi Approach

Abstract: Level III, comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
0
25
1
1
Order By: Relevance
“…Of the studies, 9 of 10 reported the AOFAS anklehindfoot score, 4 reported the SF-36, 3 reported the VAS score, and 2 reported the Calcaneal Fracture Scoring System scores. 9,14,15,23,[29][30][31][32]34,40,41 The mean AOFAS score for APRF was 87.95 (range, 72.18-100) for follow-up periods of over 1 year. One study reported an AOFAS score for AAORIF using the sinus tarsi approach of 91.7 at >1-year follow-up.…”
Section: Calcaneus Fracturesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the studies, 9 of 10 reported the AOFAS anklehindfoot score, 4 reported the SF-36, 3 reported the VAS score, and 2 reported the Calcaneal Fracture Scoring System scores. 9,14,15,23,[29][30][31][32]34,40,41 The mean AOFAS score for APRF was 87.95 (range, 72.18-100) for follow-up periods of over 1 year. One study reported an AOFAS score for AAORIF using the sinus tarsi approach of 91.7 at >1-year follow-up.…”
Section: Calcaneus Fracturesmentioning
confidence: 99%
“…For ankle fractures, we identified a total of 17 studies. [2][3][4][5][6][7][8][10][11][12][13]16,27,29,[35][36][37][38] Among these, 2 were systematic reviews, 1 meta-analysis, 2 RCTs, 5 retrospective comparative studies, 4 retrospective series, 2 prospective series, and 1 case-control study. The studies reported a total of 952 patients.…”
Section: Ankle Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…To reconstruct articular surface of the talocalcaneal joint, specialized centers apply an arthroscopic procedure [17].…”
Section: Introductionmentioning
confidence: 99%